Assessment of the Relationship between Mental Health and Academic Achievement among Students in Kazakhstan - Guliya Yertukeshova; Bibianar Baizhumanova; Ulbossyn Tuyakova; Lyazzat Kulzhabayeva; Gulnara Jumagulova; Bakyt Zhigitbekova (Health Psychology Research)
# Background